Pengembangan LKPD Berbasis Kearifan Lokal Bangka Belitung Materi Menemukan Unsur Adiksimba Kelas V SD Negeri 18 Pangkalpinang - Puspitarini, Hafizia; Sasih Karnita Arafatun; Sisi Pitriyana (JBES (Journal Basic Education Skills), 2025)
This research is based on the problem of still not being able to analyze the basic elements of a next, namely what, where, when, who, wht, how, teachers have not developed local wisdom. This research aims to produce a LKPD based on Bangka Belitung local wisdom, material to find elements of Adiksimba that are valid, practical and have potential effects. This type of research uses the Research and Development method using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The subjects of this research were 18 class V students at SD Negeri 18 Pangkalpinang. Data collection techiques used are data analysis of the validity of developing LKPD, data analysis of the practicality of responses (teachers and students), testing the effectiveness of LKPD. Based on the results of the media and material expert questionnaire for validity, a score was obtained, namely a material assessment percentage of 67,5% ” Quite Valid” and a media assessment percentage of 77,5% ”Valid”. The practicality assessment can be seen from the percentage of 100% ”Very Practical” and the practicality assessment see from the student response questionnaire obtained with a percentage of 86,6% ”Very Practical”. The Bangka Belitung local wisdom-based LKPD material found the element of adiksimba to have a potential effects as seen from the test results which obtained an average percentage of 67% in the ”Quite Effective” category, so it can be concluded that the Bangka Belitung local wisdom-based LKPD material found the element of adiksimba in students’ understanding.